Benign Fibrous Histiocytoma of Mandible: A Case Report and Updated Review - Pattamparambath, Manjusha (J Clin Diagn Res, 2016)
Benign Fibrous Histiocytoma (BFH) is a well recognised tumour of the soft tissue, developing entirely within the subcutaneous tissue, the deep soft tissues or in the parenchymal organs. However, BFH of bones is poorly defined. It has been rarely reported in the bones with femur, tibia and pelvic bone being the most commonly affected bones. Involvement of the jawbones is rare. Their clinical and radiographic features often simulate the common odontogenic and non-odontogenic lesions of the jaws. Hence, it is imperative for a dentist to have proper knowledge of various conditions affecting the jaws. Here we report a case of BFH which presented as an indolent swelling of the right mandibular posterior region for 15 years. The case emphasizes the need for considering BFH in the differential diagnosis of swellings of the jaws.